DEVELOPMENT AND VALIDATION OF PARENTING SCALE IN STUDENTS - Muhammad Fadhil Fadhlurrahman; Syifa Nur Ilahiyah; Pranata, Nabila Adhistia; Nazma Aliyah Nurafifah; Siti Hajarnur Khoirun Nisa; Adzanishari Mawaddah Rahmah; Novy Yulianty; Novita Sari (Bajang Institute, 2026)
This study objective is to develop parenting style measurement for university students based on Baumrind’s Parenting Style theory. This was a multidimensional measurement from two parenting style dimensions, demandingness and responsiveness. 59 initial items were developed and 46 final items were selected for the study. Data were collected using convenience sampling from 169 active university students across 84 universities in 16 provinces in Indonesia. Psychometric properties analysis that were used include item-rest correlation, alpha cronbach for reliability analysis, and Confirmatory Factor Analysis. The results of the item-rest correlation analysis showed that the demandingness dimension had correlation values ranging from 0,305 to 0,540 with an average of 0,431. The responsiveness dimension showed item-rest correlation values ranging from 0,412 to 0,792 with an average of 0,686. Reliability analysis used alpha cronbach for demandingness (ɑ=0,838) and responsiveness (ɑ=0,95) proved good reliability. Confirmatory Factor Analysis also showed that the two dimensions have a really good validity score and showed a good fit (CFI and TLI above 0,90; RMSEA and SRMR below 0.80). In conclusion, this measurement has adequate psychometric quality and is suitable for use in assessing the university student’s parenting style